Legal Controversy Over Divorce Filed by Wives in Religious Courts in Indonesia - Samsudin, Titin; Sahid, Mualimin Mochammad; Rahim, Arhjayati; Saka, Putri Ananda (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Divorce initiated by a wife is often a source of controversy within religious courts. In line with that, three questions are answered in this paper. First, what is the form of the "controversy" in the normative and juridical legal considerations of  cerai gugat or divorce initiated by a wife; (b) what is the form of the legal impact in the judge's decision on the "controversy" of a contested divorce; (c) what is the form of the "controversy" in community life on the response to a contested divorce. This study is a sociological study of law using a case study approach in religious courts. Data were collected by analyzing court decisions, journal articles, and books, then analyzed using Islamic legal theory. The results of this study indicate that there are three levels of controversy surrounding divorce initiated by wives. First, the differences that occur in normative and juridical law regarding the incompatibility between Islamic law and positive law governing divorce lawsuits by wives cause controversy in the law of divorce at the request of wives in religious courts. Second, differences in judges' decisions in the law of divorce initiated by a wife.  It causes controversy and resulting in legal impacts from various aspects. Third, the controversy over the response of community leaders. Some religious and community leaders see it as a threat to the stability of the family and the long-established social order. In contrast, others see it as a form of women's freedom to determine the direction of their own lives. In the context of Islamic law, the decision of a religious court is binding and enriches the development of sociological studies of law, especially divorce initiated by the wife, and influences social and legal change in Indonesia.